The Role of Service Quality in Increasing Customer Satisfaction at PT. Global Perkasa Ekspres Logistik - Septaningrum, Nuuresa Wahyu (Yayasan Literasi Sains Indonesia, 2023)
Customer satisfaction is an exciting and crucial issue for many companies, including PT. Global Perkasa Ekspres Logistik. However, until now, the role of service quality in improving the quality of customer experiences has yet to be widely reported in this company. This study aims to analyze and design service improvement strategies for PT. Global Perkasa Ekspres Logistik in managing service quality, especially in delivery services, to increase customer satisfaction. This research design falls under the category of qualitative research that PT. Global Perkasa Ekspres Logistik gather opinions through questionnaires, interviews, and direct observation. The number of analysis units in this study amounted to nine companies, which took place from March to July 2022 for qualitative descriptive data analysis. PT. Global Perkasa Ekspres Logistik is a logistics service provider for companies under its umbrella. In its journey, this company has obtained customer satisfaction through the quality of its services. According to research, factors that affect consumer satisfaction include good customer service, affordable service prices for people who often use expedition services, friendly, flexible, responsive, and quality services, and technological advances that provide convenience in communicating and providing services to consumers. Other factors that become weaknesses in achieving customer satisfaction include the presence of individuals or staff who lack experience in providing services and have an impact on the company's image.